2021
DOI: 10.3390/molecules26061633
|View full text |Cite
|
Sign up to set email alerts
|

Improved Dermal and Transdermal Delivery of Curcumin with SmartFilms and Nanocrystals

Abstract: Poor aqueous solubility of active compounds is a major issue in today’s drug delivery. In this study, the smartFilm technology was exploited to improve the dermal penetration efficacy of a poorly soluble active compound (curcumin). Results were compared to the dermal penetration efficacy of curcumin from curcumin bulk suspensions and nanocrystals, respectively. The smartFilms enabled an effective dermal and transdermal penetration of curcumin, whereas curcumin bulk- and nanosuspensions were less efficient when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
68
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(74 citation statements)
references
References 46 publications
5
68
1
Order By: Relevance
“…Testing the dermal penetration with Franz diffusion cells is tedious work and requires experienced and careful handling. Recent results, however, now demonstrated that results obtained by this technique can even be misleading if poorly soluble and non-dissolved active compounds are tested [6]. The reason for this is that the recommended test setup of Franz diffusion cells requires an acceptor medium that provides sink conditions for the test compound.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Testing the dermal penetration with Franz diffusion cells is tedious work and requires experienced and careful handling. Recent results, however, now demonstrated that results obtained by this technique can even be misleading if poorly soluble and non-dissolved active compounds are tested [6]. The reason for this is that the recommended test setup of Franz diffusion cells requires an acceptor medium that provides sink conditions for the test compound.…”
Section: Introductionmentioning
confidence: 99%
“…For a correct test setup, the acceptor medium needs to be in close contact with the test membrane to allow for a non-hindered diffusion of the active compounds through the membrane into the acceptor medium. Recent studies have now demonstrated that the acceptor medium can also penetrate into the test membrane [6]. In these cases, the acceptor medium is soaked in the test membrane, and thus the formulation that is applied onto the test membrane or skin will also come into direct contact with the acceptor medium.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a procedure is repeated several times until the desired drug concentration is achieved. Then, the films obtained are ready to be used as transdermal plasters [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thereby, low systemic bioavailability persists [25]. For this reason, parenteral delivery routes of CUR that can be easily administered by the patients themselves, such as transdermal [26][27][28] and buccal [29][30][31] routes, have been explored. Even though the transdermal and buccal delivery routes of CUR can circumvent its gut metabolism issue, the systemic bioavailability remains poor if the native form of CUR is used due to the low solubility of native CUR in the plasma fluid.…”
Section: Introductionmentioning
confidence: 99%